A Theory of Quits and Layoffs with Efficient Turnover - McLaughlin, Kenneth J. (Journal of Political Economy, 1991)
This paper answers the efficient-turnover literature's long silence regarding the quit-layoff distinction. Treating quits as worker-initiated separations and layoffs as firm-initiated separations, I establish that the existence of layoffs is compatible with optimizing workers and firms forming and dissolving employment matches to exploit all the gains from trade. The efficient-turnover approach is shown to be consistent with many empirical regularities that distinguish quits from layoffs. Structural implications of the model are tested on data from the PSID.